BEN JONSON’S “THE ALCHEMIST” CHARACTERS - Fayzullayeva Munisa Fozil qizi; Baisov Ahmad Sobirjonovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT This article provides a concise analysis of the characters in Ben Jonson’s play “The Alchemist.” Set in Jacobean London, the play satirizes alchemy and human folly through characters like the cunning Subtle, the credulous Lovewit, and the ambitious Dapper, Drugger, and Face. Through examining their personalities and interactions, the study reveals themes of deception and greed. Jonson’s use of distinct character types and comedic techniques entertains while critiquing societal corruption. This analysis offers insights into Jonson’s craftsmanship and enduring social commentary in early modern drama. Ben Jonson’s “The Alchemist” is a classic Jacobean drama that uses satire to condemn the moral deterioration and societal avarice of its period. This abstract examines how Jonson satirises the church, law, and nobility throughout the play, as well as greed and its corrupting effects. This abstract shows Jonson’s brilliant reflection on human nature and the hazards of uncontrolled ambition through characters, story, and language. The ancient cautionary tale “The Alchemist” encourages audiences to consider the dangers of wealth and moral compromise.